2009
DOI: 10.1093/glycob/cwp153
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from GNE-deficient embryonic stem cells: sialic acid biosynthesis is involved in proliferation and gene expression

Abstract: Sialic acids are widely expressed as terminal carbohydrates on glycoconjugates of eukaryotic cells. They are involved in a variety of cellular functions, such as cell adhesion or signal recognition. The key enzyme of sialic acid biosynthesis is the bifunctional UDP-N-acetylglucosamine-2-epimerase/N-acetylmannosamine kinase (GNE), which catalyzes the first two steps of sialic acid biosynthesis in the cytosol. Inactivation of GNE causes early embryonic lethality. In this study, we analyzed wild-type and GNE-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 53 publications
3
31
0
1
Order By: Relevance
“…5), suggested that IFN-g sialylation was bottlenecked at the CMP-SA synthesis stage. Furthermore, UAE expression decreases with time and is in agreement with findings from Weidemann et al (2009) who found that UAE expression is directly correlated with growth. These findings implied that during ''stationary'' non-growth phase of a typical process, when the majority of recombinant protein is produced, sialylation would be impaired due to low UAE expression.…”
Section: )supporting
confidence: 91%
“…5), suggested that IFN-g sialylation was bottlenecked at the CMP-SA synthesis stage. Furthermore, UAE expression decreases with time and is in agreement with findings from Weidemann et al (2009) who found that UAE expression is directly correlated with growth. These findings implied that during ''stationary'' non-growth phase of a typical process, when the majority of recombinant protein is produced, sialylation would be impaired due to low UAE expression.…”
Section: )supporting
confidence: 91%
“…Sialylation occurs at all stages of mammalian development and even embryonic stem cells already express sialylated glycoconjugates [5759]. The expression of GNE mRNA, encoding the key enzyme of the sialic acid biosynthesis, strongly correlates with the occurrence of sialic acid.…”
Section: Regulation Of Gnementioning
confidence: 99%
“…For example, polysialylation of the neural cell adhesion molecule (NCAM) was affected in Gne deficient ES-cells, which could be restored with supplementation of ManNAc to the growth medium [28]. And recent studies of Gne deficient ES-cell showed that Gne , apart from its role in sialic acid synthesis, may also play a role in cell proliferation, gene expression, and cell differentiation [59]. …”
Section: Gne-opathiesmentioning
confidence: 99%
“…Sialylation of glycoproteins and glycosphingolipids occurs late within the secretory apparatus by a family of Golgi-localized sialyltransferases that most commonly catalyze α2-3 or α2-6 linkages to galactose or the α2-8 linkage to sialic acid in oligo or polysialic acid structures [47]. This process is critical for mammalian development as sialylated glycans coat the surface of cells and perform a multitude of biological functions [47-49]. In addition, sialylated glycans on the surface play major roles in regulating immune and inflammatory responses and in host recognition by viruses, which often recognize specific sialic acid linkages to gain entry into cells [50].…”
Section: Introductionmentioning
confidence: 99%